Pengembangan Modul Pembelajaran Burung Serindit Melayu (Loriculus galgulus) Sebagai Maskot Fauna Provinsi Riau - Laili Rahmi (Universitas Lampung, 2018)
This research is a development research with quantitative descriptive analysis. This study aims to determine the feasibility test of the Learning Module as Learning of Malay Serindit Birds (Loriculus galgulus) as the mascot of Riau Province in the Course of Vertebrate Zoology. Samples used by Random Sampling technique. The importance of developing teaching materials for example learning modules that build character and knowledge of students on the potential of local fauna. Expected to be able to provide inspiration and language for the country that makes smarter and clearer modules about the potential for fauna and flora in the surrounding area. And can be used as a consideration and facilitate the learning process in achieving quality towards the 21st century. Penelitian ini merupakan penelitian pengembangan dengan analisis deskriptif kuantitatif. Penelitian ini bertujuan untuk mengetahui uji kelayakan dari Modul pengembangan sebagai Pembelajaran Burung Serindit Melayu (Loriculus galgulus) sebagai maskot Provinsi Riau pada Mata Kuliah Zoologi Vertebrata. Sampel yang digunakan dengan teknik random Sampling, Pentingnya pengembangan bahan ajar contohnya modul pembelajran yang membangun karakter dan pengetahuan mahasiswa pada potensi fauna lokal. diharapkan mampu memberikan inspirasi dan bahan kajian bagi dosen dalam membuat modul yang lebih inovatif serta mengangkat nilai tentang potensi fauna maupun flora didaerah sekitar. Serta dapat dijadikan bahan pertimbangan dan memfasilitasi proses pembelajaran dalam mencapai keterampilan menuju abad-21. Kata kunci: burung Serindit Melayu, modul, penelitian pengembangan